A pilot observational study of horsemanship skills training for veterans with posttraumatic stress disorder. (March 2023) - Marchand, William R.; Smith, Judy; Hoopes, Karl H.; Osborne, Makenna; Andersen, Sarah J.; Bell, Kylie; Nazarenko, Elena; Macneill, Rachel; Joubert, Katryna
Abstract: Objectives: Pilot assessment of an equine-assisted services intervention for Veterans with posttraumatic stress disorder. Design: Prospective cohort. Setting: A large Veterans Administration healthcare system. Intervention: Two sessions of instruction in horsemanship skills and two sessions of trail rides. Main outcome measures: Safety and feasibility of recruitment, retention, providing the intervention, and measuring outcomes, as well as acceptability of the intervention to the population studied were the main outcome measures. Results: There were no injuries among the 18 participants, 6 staff, or 11 equines over the 3 months of the study. Eleven of 12 (92 %) planned intervention sessions were provided, with one being canceled due to weather. Out of approximately 1800 potential subjects, 21 were enrolled within three months and three dropped out before the first session. The mean number of sessions attended was 3 % and 52 % of participants completed all sessions. The mean PACES score for all sessions together was 109 (SD = 12), with a range of 50–126. Pre- to one-month post-intervention exploratory results indicated increased psychological flexibility (p = 0.008) and positive affect (p = 0.008) as measured by the Acceptance and Action Questionnaire II and the Positive and Negative Affect Scale, respectively as well as decreased PTSD (p = 0.001) and depressive symptoms (p = 0.017) as measured by the PTSD Checklist for DSM 5 and the Beck Depression Inventory, respectively. Conclusions: Results suggest the intervention can be conducted with minimal risk. Further, it was feasible to recruit participants as well as provide the intervention and measure exploratory outcomes. Session attendance and PACES scores indicate acceptability to the Veteran population. The exploratory results will provide sample size estimates for future randomized controlled studies of this intervention Future studies should plan for missed sessions due to weather and consider compensating subjects to enhance retention. Finally, this work provides preliminary evidence that this intervention, without a mental health treatment component, might benefit the mental health of Veterans with PTSD. Highlights: Equine-assisted services have the potential to benefit Veterans with PTSD. A horsemanship skills program was feasible to implement for this population. Participation was associated with PTSD and mood symptom improvement. Participation was also associated with enhanced psychological flexibility.